Lifestyle and vascular risk effects on MRI-based biomarkers of Alzheimer's disease: a cross-sectional study of middle-aged adults from the broader New York City area. Issue 3 (23rd March 2018) - Mosconi, Lisa; Walters, Michelle; Sterling, Joanna; Quinn, Crystal; McHugh, Pauline; Andrews, Randolph E; Matthews, Dawn C; Ganzer, Christine; Osorio, Ricardo S; Isaacson, Richard S; De Leon, Mony J; Convit, Antonio
Abstract : Objective: To investigate the effects of lifestyle and vascular-related risk factors for Alzheimer's disease (AD) on in vivo MRI-based brain atrophy in asymptomatic young to middle-aged adults. Design: Cross-sectional, observational. Setting: Broader New York City area. Two research centres affiliated with the Alzheimer's disease Core Center at New York University School of Medicine. Participants: We studied 116 cognitively normal healthy research participants aged 30–60 years, who completed a three-dimensional T1-weighted volumetric MRI and had lifestyle (diet, physical activity and intellectual enrichment), vascular risk (overweight, hypertension, insulin resistance, elevated cholesterol and homocysteine) and cognition (memory, executive function, language) data. Estimates of cortical thickness for entorhinal (EC), posterior cingulate, orbitofrontal, inferior and middle temporal cortex were obtained by use of automated segmentation tools. We applied confirmatory factor analysis and structural equation modelling to evaluate the associations between lifestyle, vascular risk, brain and cognition. Results: Adherence to a Mediterranean-style diet (MeDi) and insulin sensitivity were both positively associated with MRI-based cortical thickness (diet: βs ≥0.26, insulin sensitivity βs ≥0.58, P≤0.008). After accounting for vascular risk, EC in turn explained variance in memory (P≤0.001). None of the other lifestyle and vascular risk variables were associated with brain thickness. In addition, the path associations between intellectual enrichment and better cognition were significant (βs ≥0.25 P≤0.001), as were those between overweight and lower cognition (βs ≥-0.22, P≤0.01). Conclusions: In cognitively normal middle-aged adults, MeDi and insulin sensitivity explained cortical thickness in key brain regions for AD, and EC thickness predicted memory performance in turn. Intellectual activity and overweight were associated with cognitive performance through different pathways. Our findings support further investigation of lifestyle and vascular risk factor modification against brain ageing and AD. More studies with larger samples are needed to replicate these research findings in more diverse, community-based settings.